In Vitro Antioxidant Activity of Flowers and Fruits of Alstonia scholaris - Joel James,; Arun Kumar Thaliyil Veettil,; Kumar Pratyush,; Chandra Shekhar Misra,; Lipin Dev Mundur Sahadevan,; Thankamani V, (International Journal of Phytomedicine, 2011)
The ethnobotanical and pharmacological evaluation of plant based chemicals have shown rapid strides in the last few decades. Plants have been a rich source of important therapeutic agents and form the basis of herbal systems of medicine, like ayurveda, resulting in the revival of ancient traditions of medicine. The present study was carried out to investigate the anti oxidant potential of the inflorescence and fruits of Alstonia scholaris using an in vitro model system like DPPH assay and Beta carotene Assay. The methanol extract of the flower showed powerful antioxidant activity by DPPH and Betacarotene assays in comparison with the standard butylated hydroxy toluene (BHT), l- ascorbic acid. For DPPH assay the IC-50 value was also calculated and was found to have a significant correlation between benzene extract of flower and methanol extract of fruits. Overall, the methanol extracts of flower showed higher anti oxidant activity than the fruit